Detection of human parvovirus 4 DNA in the patients with acute encephalitis syndrome during seasonal outbreaks of the disease in Gorakhpur, India. Issue 1 (1st January 2019) - Arankalle, Vidya A.; Srivastava, Navin; Kushwaha, Komal P.; Sen, Agnibha; Ramdasi, Ashwini Y.; Patel, Priyanka A.; Kuthe, Sumeet; Haldipur, Bangari; Sakpal, Gajanan N; Lole, Kavita S.; Ingle, Nilesh B
ABSTRACT: Seasonal outbreaks of acute encephalitis syndrome (AES) at Gorakhpur, India have been recognized since 2006. So far, the causative agent has not been identified. Use of next generation sequencing identified human parvovirus 4 (HPARV4) sequences in a CSF/plasma pool. These sequences showed highest identity with sequences earlier identified in similar patients from south India. Real-time PCR detected HPARV4 DNA in 20/78 (25.6%) CSF and 6/31 (19.3%) plasma of AES patients. Phylogenetic analysis classified three almost complete genomes and 24 partial NS1 sequences as genotype 2A. The observed association of HPARV4 with AES needs further evaluation. ELISAs for the detection of IgM and IgG antibodies against scrub typhus ( Orientia tsutsugamushi, OT) showed ∼70% IgM/IgG positivity suggestive of etiologic association. Prospective, comprehensive studies are needed to confirm association of these agents, singly or in combination with AES in Gorakhpur region.